Adaptive finite-time fan-coil outlet wind temperature control for the ASHPAC system - Chen, Xiaofei; Li, Chao; Yang, Qinmin (Frontiers in Energy Research, 2022)
In this paper, an adaptive finite-time fan-coil outlet wind temperature control scheme is proposed for the air-source heat pump air-conditioning system. First, a correction module is introduced to compensate the first-order damp elements in the temperature sensor to capture the temperature in real-time. Then, a simple neural network is employed to approximate the unknown and nonlinear functions of the system. On this basis, an adaptive finite-time neural controller is developed, and the finite-time convergence of temperature regulation error is ensured. The stability of the studied fan-coil control is guaranteed by rigorous Lyapunov proof. Finally, two simulation examples are carried out to verify the effectiveness of the proposed control scheme.